Detection rate of Pneumococcal Pneumonia using the Urine Antigen Kit BinaxNow Streptococcus Pneumoniae Test: a Prospective Cohort Study in a Tertiary Hospital in Malaysia - AH, Mohamed Faisal; P, Petrick; Ban, Andrea YL; AM, Roslina (IIUM Medical Journal Malaysia, 2017)
Background: Pneumococcal pneumonia is the commonest type of bacterial pneumonia worldwide. In Malaysia, the reported incidence of pneumococcal pneumonia is low. This may be due to poor sensitivity of conventional methods. The use of BinaxNOW, a urinary antigen test for Streptococcus pneumoniae can aid in the diagnosis of pneumococcal pneumonia. Objective: To determine the detection rate of pneumococcal pneumonia using BinaxNOW kit and to compare this with the conventional culture method for blood and sputum. Methods: This was a prospective cohort study involving patients 18 year-old and above admitted for community-acquired pneumonia (CAP) or health-care associated pneumonia (HCAP) to UKMMC between December 2011 and June 2012. BinaxNOW test, serology for Mycoplasma, Legionella and Chlamydia and cultures from blood/sputum/other respiratory tract samples and other routine investigations were performed. Results: A total of 102 patients were recruited; 89 (87.3%) with CAP, 13 (12.7%) with HCAP. 57 (55.9%) had pneumonia of unknown aetiology, 11 patients (10.8%) had positive blood cultures, 8 patients (7.8%) had a positive urine BinaxNOW test and 6 patients (5.9%) had positive sputum cultures. Streptococcus pneumoniae was the commonest isolate accounting for 9 cases (8.8%) followed by Klebsiella pneumoniae in 7 cases (6.9%). 8 out of 9 patients with positive urine BinaxNOW test had negative cultures for Streptococcus pneumoniae. One patient grew Streptococcus pneumoniae from the tracheal aspirate however the urine BinaxNOW test was negative. Conclusion: The use of urine BinaxNOW kit in UKMMC increased the detection rate of pneumococcal pneumonia in hospitalized patients.